Web crippling design of lean duplex stainless steel tubular members under interior loading conditions. (1st July 2021) - Cai, Yancheng; Young, Ben
Highlights: FEMs of lean duplex tubular members under interior loading conditions were developed. Three different load conditions were considered, namely the IOF, ITF and IL. Parametric study of 144 specimens was performed. Current web crippling design provisions were assessed. Modified web crippling design rules are proposed in this study. Abstract: Numerical analysis and design of cold-formed lean duplex stainless steel (CFLDSS) tubular members undergoing web crippling are presented in this paper. The tubular members were subjected to the loading conditions of Interior-One-Flange (IOF), Interior-Two-Flange (ITF) and Interior Loading (IL). Finite element (FE) models were developed to simulate the members under these three interior loading conditions. The results obtained from the FE analysis were used to compare with test results in terms of failure modes, strengths and load-deformation curves. After successful verification, the FE models were employed for an extensive parametric study. The key parameters in the parametric study included the ratios of flat web height to thickness, load bearing length to web thickness, load bearing length to flat web height and section inner radius. The parametric study results together with the test results were used to compare with the nominal strengths predicted by using the current specifications (ASCE, AS/NZS, NAS and EC3), and the design equations in the literature. New sets of coefficients are proposed for the unified design equation in NAS and the direct strength method (DSM) for the web crippling design of CFLDSS tubular members. Overall, the modified design rules were able to provide more accurate predictions compared with the design rules in current specifications and literature. The results showed that the proposed design methods are suitable for the design of web crippling of CFLDSS tubular members under the IOF, ITF and IL conditions.